Face Recognition Based Security Scanner using PCA - Naik, Amrita; Nagekar, Amrita; Monte, Michael; Parab, Aditya; Revadkar, Ronan (International Journal of Computer Sciences and Engineering, 2025)
Immediately This paper proposes a novel Face Recognition based Security Scanner for keeping track of people moving in and out of a workplace using Haar Cascade and Principal Component Analysis. The proposed system trains the system using images and then detects and recognises the person and gives details about the person with the date and time.